Effects of humeral intraosseous epinephrine in a pediatric hypovolemic cardiac arrest porcine model - Michael James Neill; James M Burgert; Dawn Blouin; Benjamin Tigges; Kari Rodden; Rachel Roberts; Phillip Anderson; Travis Hallquist; John Navarro; Joseph O'Sullivan; Don Johnson (Trauma Surgery & Acute Care Open)
Background Aims of the study were to determine the effects of humerus intraosseous (HIO) versus intravenous (IV) administration of epinephrine in a hypovolemic, pediatric pig model. We compared concentration maximum (Cmax), time to maximum concentration (Tmax), mean concentration (MC) over time and return of spontaneous circulation (ROSC).Methods Pediatric pig were randomly assigned to each group (HIO (n=7); IV (n=7); cardiopulmonary resuscitation (CPR)+defibrillation (defib) (n=7) and CPR-only group (n=5)). The pig were anesthetized; 35% of the blood volume was exsanguinated. pigs were in arrest for 2 min, and then CPR was performed for 2 min. Epinephrine 0.01 mg/kg was administered 4 min postarrest by either route. Samples were collected over 5 min. After sample collection, epinephrine was administered every 4 min or until ROSC. The Cmax and MC were analyzed using high-performance liquid chromatography. Defibrillation began at 3 min postarrest and administered every 2 min or until ROSC or endpoint at 20 min after initiation of CPR.Results Analysis indicated that the Cmax was significantly higher in the IV versus HIO group (p=0.001). Tmax was shorter in the IV group but was not significantly different (p=0.789). The MC was significantly greater in the IV versus HIO groups at 90 and 120 s (p<0.05). The IV versus HIO had a significantly higher MC (p=0.001). χ2 indicated the IV group (5 out of 7) had significantly higher rate of ROSC than the HIO group (1 out of 7) (p=0.031). One subject in the CPR+defib and no subjects in the CPR-only groups achieved ROSC.Discussion Based on the results of our study, the IV route is more effective than the HIO route.